EFFECT OF NICKEL ELECTROPLATING TIME ON CORRUGATED METAL GASKETS PERFORMANCE - Ahbar, Isa Ibnu; Nurhadiyanto, Didik (Universitas Muhammadiyah Jakarta, 2021)
Metal gaskets is an alternative to asbestor gaskets, but it still have many weaknesses. The main focus of this research is to find the optimal electroplating time to prevent leakage.This research was started with forming the gasket material, and then followed by coating process. The methode that used in coating proses was electroplating with nickel solution. The gasket material used SUS 304 sheet with 1,5mm of thickness. Water pressure test was used to test leackage with 2 MPa, 4 MPa, 6 MPa, and 8 MPa presurre for 5 minute test duration. The result this research are (1) electroplating are effected by time, the longer time applied more nickel attached to the gasket, (2) the best performance on nickel electroplated gasket was on 32 minute and 45 second plating time, (3) electroplated nickel gasket performance was better than the original to prevent leakage from 2 to 8 MPa water pressure.